HUBUNGAN PERILAKU PENGGUNAAN INTERNET TERHADAP INTERAKSI SOSIAL PADA MAHASISWA KEPERAWATAN DI KOTA DENPASAR - Ida Bagus Duwi Krisna Putra; Made Oka Ari Kamayani; Ni Luh Putu Eva Yanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Internet usage is a form of development of information and communication technology that changes a person's behavior in activities. The existence of the internet causes several impacts that are felt by many teenagers such as nursing students. The convenience provided when using the internet can cause nursing students to overuse the internet. Excessive use of the internet will affect the ability of nursing students in socially interaction. The research aims to understand behavior correlations internet use against social interaction on nursing students in Denpasar City. The design was used in the study of correlational descriptive research with the approach cross-sectional. The research sample was nursing students in Denpasar City who were obtained using probability sampling with proportional stratified random sampling technique (n=234). The independent variable of this research is internet usage behavior, while the dependent variable is social interaction with parents, social interaction with peers, social interaction with the campus environment, and social interaction with the community environment in nursing students. Data analysis used the Spearman correlation test (?<0.05). The results found that internet usage behavior is related to social interaction with peers (p=0.000), but not related to social interaction with parents (p=0.161), campus environment (p=0.540), and community environment (p=0.977). So it can be concluded that there is a correlation between internet usage behavior and social interaction with peers in nursing students in Denpasar City. Students are expected to reduce excessive internet use and increase social interaction with peers.